Emotional Intelligence - The Road to Excellency in Management - Gheorghina Liliana Bir̂ladeanu (Agora International Journal of Economical Sciences (AIJES), 2019)
The current management implies a continual adaptation to the economical, political and social dynamics and evolution. Upon this context there is a need for leaders with extremely well developed communication abilities, empathic and men of vision, who can direct by using a positive motivation. It is, thus, understood that the foremost element is the emotional intelligence. Taking into consideration the possibility of developing these values through the means of education so that to obtain a high quality management and an efficient communication, we consider this to be the way to excellency in management.
Keywords: 330